(untitled) (Psychology Travelogs, 2022)
Rapid changes in the technological structure and radical social transformations in our country led not only to significant changes in the field of labor activity, the education system, but also significantly actualized the problem of the relationship "personality - education - production". In this situation, the orientation of education on the self-worth of the individual, his internal resources, the desire for self-realization and self-development, on the principle of the connection of the development of the individual and his integral life movement with labor activity is an integral part of the methodological foundation of domestic psychological science. At the same time, there is an urgent need to study the influence of the educational process, the nature of the educational environment of a higher educational institution on the mental formations of students, their personal development at various stages of education, and the driving forces of development. This need is due to the need to validate the knowledge accumulated by age and pedagogical psychology in accordance with the current socio-cultural situation. A student must be aware of the changes taking place in him, also have his own opinion, his assessments, views on various life situations, his attitude and his own choice of life direction.